The effect of special exercises to develop the compatibility between eyes and legs to adjust the jousting distance for the players of the Arab sword weapon - Qasim Mohammed Ibrahim, Atheer; Waheeb Yassin, AbdulRazzaq; Qassem Khalaf, Naseer (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify On the effect of compatibility between the eye and the legs on improving the sense of distance for the movements of the two legs and the sense of the distance of jousting for players of the Arab sword weapon in the sport of fencing, as the player needs these skills during the match because the defense is considered a prelude to the process of response and attack in various competitions, as well as accelerating the pace of play, and deliberately The study was based on the experimental method, as the researcher chose the method of the control and experimental groups, and the study was conducted on a sample of (6) players from Diyala club teams (youth category) The results were statistically used in that statistical bag (spss); it was concluded that the exercises using the device had a positive impact on the development of some offensive and defensive skills of the study sample, and the study recommended Focusing on equipment and aids when developing training programs because of their positive impact on fencing players and their great importance during the match and moving away from the traditional methods used in training.